Immune Checkpoint Inhibitors in Acute Myeloid Leukemia: A Meta-Analysis - Gómez-Llobell, Marina; Peleteiro Raíndo, Andrés; Climent Medina, Jose; Gómez Centurión, Ignacio; Mosquera Orgueira, Adrián (Frontiers in Oncology, 2022)
Background: Experience with immune checkpoint inhibitors (ICIs) in the treatment of acute myeloid leukemia (AML) is still limited and based on early clinical trials, with no reported randomized clinical data. In this study, we reviewed the available evidence on the use of ICIs, either in monotherapy or in combination with other treatments, in different AML settings, including newly diagnosed AML, relapsed or refractory (R/R) AML and maintenance treatment after allogeneic-HSCT (allo-HSCT). Materials and Methods: A systematic literature review was conducted using PubMed electronic database as primary source to identify the studies involving immune checkpoint inhibitors in first-line and R/R AML. We recorded Overall Response (ORR), Complete Response (CR) and Complete Response with incomplete count recovery (CRi) rates, overall survival (OS) and immune-related adverse events ≥ grade 3 (irAEs). Hereafter, we analyzed the overall profile of these ICIs by performing a meta-analysis of the reported outcomes. Results: A total of 13 studies were identified where ICI was used in patients with AML. ORR across these studies was 42% (IC95%, 31% - 54%) and CR/CRi was 33% (IC95%, 22%-45%). Efficacy was also assessed considering the AML setting (first-line vs. relapsed/refractory) and results pointed to higher response rates in first-line, compared to R/R. Mean overall survival was 8.9 months (median 8 months, [IC95%, 3.9 - 15.5]). Differences between first line and R/R settings were observed, since average overall survival in first line was 12.0 months, duplicating the OS in R/R which was 7.3 months. Additionally, the most specific adverse events (AEs) of these therapies are immune-related adverse events (irAEs), derived from their inflammatory effects. Grade ≥3 irAEs rate was low and similar among studies (12% [95%CI 8% - 16%]). Conclusion: ICIs in combination with intensive chemotherapy, hypomethylating agents or other targeted therapies are gaining interest in the management of hematological malignancies such as AML. However, results obtained from clinical trials are modest and limited by both, the type of design and the clinical trial phase. Hopefully, the prospective study of these therapies in late-stage development could help to identify patients who may benefit from ICI therapy.